2019
DOI: 10.1186/s13550-019-0586-6
|View full text |Cite
|
Sign up to set email alerts
|

64Cu-ATSM/64Cu-Cl2 and their relationship to hypoxia in glioblastoma: a preclinical study

Abstract: BackgroundDiacetyl-bis(N4-methylthiosemicarbazone), labeled with 64Cu (64Cu-ATSM) has been suggested as a promising tracer for imaging hypoxia. However, various controversial studies highlighted potential pitfalls that may disable its use as a selective hypoxic marker. They also highlighted that the results may be tumor location dependent. Here, we first analyzed uptake of Cu-ATSM and its less lipophilic counterpart Cu-Cl2 in the tumor over time in an orthotopic glioblastoma model. An in vitro study was also c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(59 citation statements)
references
References 42 publications
1
58
0
Order By: Relevance
“…The same study also reported concerning stability issues of the complexing ligand in mouse blood serum and whole blood in vivo, despite being stable in mouse serum in vitro. Similarly, comparing two recent studies investigating the theranostic potentials of copper-64 with glioblastoma in similar setups but by two different groups, showed surprisingly similar results for [ 64 [68].…”
Section: Controversial Copper Uptake Mechanismsupporting
confidence: 62%
See 4 more Smart Citations
“…The same study also reported concerning stability issues of the complexing ligand in mouse blood serum and whole blood in vivo, despite being stable in mouse serum in vitro. Similarly, comparing two recent studies investigating the theranostic potentials of copper-64 with glioblastoma in similar setups but by two different groups, showed surprisingly similar results for [ 64 [68].…”
Section: Controversial Copper Uptake Mechanismsupporting
confidence: 62%
“…Accumulation of [ 64 Cu]CuCl 2 was elevated at pO 2 < 5%, but with no further significant increase at lower oxygen concentrations [68]. The authors concluded that while both [ 64 Cu][Cu(ATSM)] and [ 64 Cu]CuCl 2 could be considered as hypoxia-selective tracers, non-hypoxic accumulation in copper transporters should also be accounted for [68]. Interestingly, in an investigation of the possibility to use ] with enhanced efflux, while knockdown of MDR1 showed inverse effects, which further implies a more complex copper retention mechanism than what was previously proposed [69].…”
Section: Controversial Copper Uptake Mechanismmentioning
confidence: 87%
See 3 more Smart Citations